Type 1 Diabetes: BTNL2‐Ig Protein Attenuates Type 1 Diabetes in Non‐Obese Diabetic (NOD) Mice (Adv. Healthcare Mater. 9/2019). Issue 9 (9th May 2019) - Tian, Xiaohong; Lin, Yujun; Cui, Cheng; Su, Min; Lai, Laijun
Abstract : In article number1800987 by Laijun Lai and co‐workers, recombinant butyrophilin‐like 2 (BTNL2)‐IgG2a Fc (rBTNL2‐Ig) fusion protein is examined for its effect on Type 1 diabetes (T1D), a T cell‐mediated autoimmune disease. rBTNL2‐Ig ameliorates T1D in non‐obese diabetic (NOD) mice, which correlates with its ability to inhibit T cell function; consequently, rBTNL2‐Ig may provide a useful treatment of T1D patients.